Canvassing vs Digital Marketing: Efektivitas Metode Komunikasi Pemasaran pada PT. Redo Marketing Indonesia - Ramadini, Nurul Rizkia; Rubyasih, Arina; Koesanto, Stefani Made Ayu Artharini (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2024)
Digitization brings about fundamental changes in almost every aspect of life, including marketing communication strategies. PT. Redo Marketing Indonesia, a distributor of beauty clinic equipment, has shifted its marketing strategy from canvassing to digital marketing through the social media platform Instagram. This research aims to examine the effectiveness and the impact of this change on the marketing communication process in the company, and used descriptive qualitative data analysis methods. The data was collected through interviews to several marketing staf. The research results indicate that digital marketing through Instagram is more financially efficient and enables instant communication with a wider target audience, thus accelerating the spread of information. However, on the flip side, canvassing methods remain effective for very specific and local target markets. PT. Redo Marketing Indonesia's efforts to optimize Instagram have built a strong brand image and increased customers interaction. Keywords: Brand Image, Canvassing, Marketing Communication.